2011
DOI: 10.1111/j.1743-6109.2011.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sexual Dysfunction and Sexually Related Personal Distress in Patients Who Have Undergone Orthotopic Liver Transplantation for End-Stage Liver Disease

Abstract: Introduction Sexual dysfunction (SD) status post-orthotopic liver transplant (OLT) for end-stage liver disease (ESLD) has long been recognized. To date, there are no studies examining how sexually related personal distress (SRPD) impacts sexual function in this population. Aims To assess SD and SRPD in men and women who have undergone OLT for ESLD and to compare them with previously published reports on subjects without SD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Regarding measurement of overall testosterone in cirrhosis, TT seems to be the more effective marker because it measures testosterone levels independently of alterations in protein production (SHBG‐bound, albumin‐bound and free). Studies evaluating sexual dysfunction before and after orthotopic liver transplantation (OLT) found controversial results and the prevalence seems to be similar to prior OLT . Arterial hypertension and diabetes have been previously associated with ED and also studies in other chronic disease such as chronic obstructive pulmonary disease found high prevalence rates .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding measurement of overall testosterone in cirrhosis, TT seems to be the more effective marker because it measures testosterone levels independently of alterations in protein production (SHBG‐bound, albumin‐bound and free). Studies evaluating sexual dysfunction before and after orthotopic liver transplantation (OLT) found controversial results and the prevalence seems to be similar to prior OLT . Arterial hypertension and diabetes have been previously associated with ED and also studies in other chronic disease such as chronic obstructive pulmonary disease found high prevalence rates .…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating sexual dysfunction before and after orthotopic liver transplantation (OLT) found controversial results [35][36][37][38] and the prevalence seems to be similar to prior OLT. 39 Arterial hypertension and diabetes have been previously associated with ED 10,40,41 and also studies in other chronic disease such as chronic obstructive 44 were associated with ED in chronic hepatitis C patients and we could show in our cohort that low libido, most likely owing to the burden of the disease, is significantly decreased in patients with ED.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibited sexual desire and decreased sexual activity have received little attention in this population. Previous studies focused on patients with stable liver disease (Simsek, Aslan, Akarsu, Koseoglu, & Esen, 2005) or patients pre and post liver transplant (Burra et al, 2010; Park & Villanueva, 2011; Sorrell & Brown, 2006), not on patients toward the end of life. According to Sorrell and Brown (2006) the effects of ESLD on sexual function is complex (p. 1473).…”
Section: Discussionmentioning
confidence: 99%
“…82 Although female transplant recipients do exhibit mild to moderate sexual dysfunction, they continue sexual activity at a high rate. 68,131 Pregnancy outcomes are favorable after LT, although there is an increased risk of obstetric complications for both mothers and infants. 83,132 Female LT recipients have higher rates of cesarean delivery and preterm labor than general obstetrical patients; nevertheless, no differences have been reported in the premature rupture of membranes or placenta previa or in the overall rate of fetal death.…”
Section: Hormone Levels Sexual Func-tion and Pregnancy: Does Liver mentioning
confidence: 99%